2017
DOI: 10.1039/c6sc04799h
|View full text |Cite
|
Sign up to set email alerts
|

Rectification of current responds to incorporation of fullerenes into mixed-monolayers of alkanethiolates in tunneling junctions

Abstract: This paper describes the rectification of current through molecular junctions comprising self-assembled monolayers of decanethiolate through the incorporation of C60 fullerene moieties in junctions using eutectic Ga–In (EGaIn) and Au conducting probe AFM top-contacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 70 publications
3
79
1
Order By: Relevance
“…In contrast, the mixed SAMs showed that including even small quantities of disulfide or acetate derivatives into a SAM results in a significantly reduced rectification ratio. The SC 11 This finding indicated that a subtle supramolecular structure change significantly affects Fc-based molecular diode performance.…”
Section: Performance Of Molecular Diodes In Mixed Sam-based Junctionsmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, the mixed SAMs showed that including even small quantities of disulfide or acetate derivatives into a SAM results in a significantly reduced rectification ratio. The SC 11 This finding indicated that a subtle supramolecular structure change significantly affects Fc-based molecular diode performance.…”
Section: Performance Of Molecular Diodes In Mixed Sam-based Junctionsmentioning
confidence: 89%
“…[24] In 2010, Burkhardt et al [25] reported on the concept of an electrically programmable selfassembled molecular charge storage layer for organic thinfilm transistors (OTFTs). [11] Copyright 2017, The Royal Society of Chemistry. [11] Copyright 2017, The Royal Society of Chemistry.…”
Section: Molecular Memory Devices Based On Mixed Samsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular diodes have been attracting much attention recently, both in self-assembled monolayers [1][2][3][4][5][6][7] and on the single-molecule scale. [8][9][10][11][12][13][14][15][16] Even though the rectifier has been the seminal device which launched the field of single-molecule electronics, 17 up to date, their performance have many shortcomings.…”
mentioning
confidence: 99%